ANTIBACTERIAL TEST OF ETHANOLIC EXTRACT NANOPARTICLES FROM ARUM MANIS MANGO LEAVES (MANGIFERA INDICA L. VAR. ARUM MANIS) AGAINST STAPHYLOCOCCUS AUREUS - Lubis, Nadya Frestika; Rahayu, Yayuk Putri; Nasution, Haris Munandar; Lubis, Minda Sari (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Secondary metabolites with antibacterial properties have been found in arummanis mango leaves. Alkaloids, flavonoids, tannins, saponins, triterpenoids, and steroids, especially the mangiferin molecule found in several mango varieties, are also present in arum manis mango leaf extract. Mangiferin has shown action on Staphylococcus aureus as an antibacterial agent that can prevent the development of bacteria. Staphylococcus aureus is one of the bacteria that triggers skin infections. In this research, extract nanoparticles and inhibition tests against staphylococcus aureus bacteria were prepared using extract nanoparticles and ethanol extract of arum manis mango leaves. The manufacture of nanoparticles in this study was carried out because smaller and nanometer-sized materials have more special chemical and glass characteristics; their small size has a greater surface area to volume ratio than larger particles. Nanoparticles are small particles ranging in size from 1 to 1000 nm. A particle size analyzer is used to characterize nanoparticles. Using the disc diffusion method, antibacterial activity tests were carried out at concentrations of 25%, 50%, and 75%, using nanoparticle extracts, and 2.5%, 5%, and 7.5% for extract concentration. The results of the extract nanoparticle size characterization were 40.2 nm. The bacterial inhibition zones of arum manis mango leaf extract obtained at concentrations of 25%, 50%, and 75% were 11.9, 14.4, and 15.4 mm, respectively. Meanwhile, the inhibition zones of nanoparticle bacteria extract 2.5%, 5%, and 7.5% were 15.5, 17.5, and 18.3 mm, respectively. The concentration of 2.5% nanoparticle extract has the inhibition power of bacteria equivalent to that of 75% ethanol extract, so it says that the nanoparticles can reduce the size dose and have an inhibition power in the moderate sensitivity category.